THE URGENCY OF 3 ROUNDS OF ELECTIONS IN 3 E (BUDGET EFFECTIVENESS, TIME EFFICIENCY, AND WORK PROGRAM EXECUTION) - Maryam Salampessy; Zulkifli Ayub; Susilawati; Mohammad Sawir; A Asdar (Adisam Publisher, 2024)
Researchers believe that one round of ELECTION can increase the effectiveness of the APBN, time efficiency, and widen the gap between the elected Presidential and Vice Presidential Candidates. Therefore, this research aims to analyze the Urgency of the Satu Putranan Election in 3 E (Budget Effectiveness, Time Efficiency, and Work Program Execution) (Manzilati, 2017) . This research is qualitative research with a descriptive approach, namely the urgency of the One Putranan Election Urgency in 3 E (Budget Effectiveness, Time Efficiency, and Work Program Execution). The data in this research was obtained from credible websites, books, journals and a number of other reliable sources. This data can also be called secondary data. The data in this research was analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions. The research results show that first, implementing one round of ELECTIONS can save 14.4 trillion which is more effective if it is allocated to the education, religion, sports, economy and other sectors in need. Second, Carrying out one round of ELECTIONS can save time for approximately two months. The elected Presidential Candidates and Vice Presidential Candidates can maximize the use of this time to finalize their work programs and resolve a number of outstanding issues. Third, One round of ELECTIONS can be carried out directly without the 50% requirement by changing the ELECTION law.